Transnational education and regional development: a case study of Namal college, Mianwali, Pakistan - Tayyaba, B (2018)
Transnational education is proliferating in developing countries as TNEs are used strategically to raise the quantity and quality of local higher education provision to absorb the increasing local demand for higher education and prepare the country for a knowledge-based economy. However, there is a critical paucity in the literature discussing the substantial rise of TNE in developing countries and its impact on the regional development. This is a qualitative case study that intends to explore the impact of TNE, i.e. Namal College, on the regional development in Pakistan. Stakeholders’ perspective on the role of the TNE is considered, and barriers of the TNE to regional development are explored as well. The data was collected using semi-structured interviews and documentary analysis. A total of 17 participants were selected for the interviews; 10 final year undergraduate students, and 5 academic and administrative staff members of Namal College were selected using purposive sampling, while 2 employers were selected using convenience sampling. The findings indicate that the TNE has broad social and economic impact on the regional development. It has played a crucial role in demand absorption, enhanced the capacity and quality of local higher education institution rapidly through ready-made resources and good pedagogical practices, while offering students from underprivileged background an option to study international degree from home. However, the TNE does not assist students in securing jobs. In addition, the curriculum brought by the TNE is less responsive to the local needs, thus limiting the impact in terms of knowledge transfer for regional development. Moreover, high franchise fee associated with the TNE may also hinder institutional expansion projects by causing financial constraints on the host institution.